The relationship between childhood asthma and socioeconomic status: a Korean nationwide population-based study - Lee, Won Seok; Hwang, Jae Kyoon; Ryu, Jiin; Choi, Young-Jin; Oh, Jae-Won; Kim, Chang-Ryul; Han, Man Yong; Oh, In Hwan; Lee, Kyung Suk (Frontiers in Public Health, 2023)
This study aimed to investigate associations of socioeconomic status (SES) with asthma exacerbation and asthma-related hospital utilization factors among children with asthma in the Republic of Korea. This study retrospectively analyzed population-level data from the Korean National Health Insurance Service, collected from 2013 through 2019. SES was classified into five categories according to the national health insurance premiums quantiles (0 [lowest] to 4 [highest]). The hazard ratios (HRs) for asthma exacerbation, emergency department (ED) visits, hospital admission, and intensive care unit (ICU) admission were analyzed with respect to SES. Among the five SES groups, SES group 0 (medical aid), had the highest tallies and proportions of children who experienced asthma exacerbations (n=1682, 4.8%), ED visits (n=932, 2.6%), hospital admission (n=2734, 7.7%) and ICU admission (n=14, 0.04%). Compared with SES group 4, SES group 0 had adjusted HRs of 3.73 (p=.0113) and 1.04 (p<.0001) for ventilator support/tracheal intubation and administration of systemic corticosteroids, respectively. Relative to group 4, the adjusted HRs for ED visits, hospital admission, and ICU admission in group 0 were 1.88 (p<.0001), 2.20 (p<.0001), and 7.12 (p<.0001), respectively. In the survival analysis, group 0 had a significantly higher risk of ED presentation, hospital admission, and ICU admission than the other groups (log-rank p<0.001). Compared with children of higher SES, those in the lowest SES group had increased risk of asthma exacerbation, hospital admission, and receiving treatment for severe asthma symptoms.